Absence of platelet overactivation and thrombosis formation among patients with coronary atherosclerosis disease after vaccination against SARS-CoV-2 - Huajie Xu; Xin Zhao; Peng Zhang; Yunjie Zhang; Qi Zhou; Huibin Wu; Bing Fan; Si Zhang; Hongyi Wu (Heliyon)
Background: Association of Coronavirus disease 2019 vaccines with thrombosis has raised concerns among patients with coronary atherosclerosis disease (CAD). Objectives: After vaccination against SARS-CoV-2, to detect thrombosis formation in atherosclerosis ApoE−/− mice, and platelet activation, coagulation, the profile of prothrombotic antibodies, and the production of platelet factor 4 (PF4) antibodies in patients with CAD. Methods: Atherosclerotic ApoE−/− mice were immunized with saline or inactivated SARS-CoV vaccines. We investigated FeCl3-induced thrombus formation in vivo, and thrombus formation under flow conditions ex vivo. Inpatients undergoing percutaneous coronary intervention (PCI) were consecutively enrolled and defined according to vaccination status. We evaluated coagulation by thrombelastograph (TEG), platelet activation makers by flow cytometry, PF4 antibody and antiphospholipid antibodies by ELISA, and SARS-CoV-2 neutralizing antibody. Results: In atherosclerotic ApoE−/− mice, FeCl3-induced thrombus formation and thrombus formation under flow conditions were similar between saline-treated and inactivated SARS-CoV-2 vaccines-treated groups. A total of 182 patients undergoing PCI were included in the final analysis, of whom 92 had been vaccinated. Baseline characteristics were well balanced between unvaccinated and vaccinated groups. The expression of PAC-1 and P-selectin, the prevalence of positivity for PF4 antibodies and antiphospholipid antibodies were similar between these two groups. Conclusions: Inactivated SARS-CoV-2 vaccines did not potentiate thrombosis formation in atherosclerotic mice. Inactivated SARS-CoV-2 vaccines did not enhance platelet activation, or trigger the production of PF4 and antiphospholipid antibodies in patients with CAD. In light of the observed thrombotic risks associated with adenovirus-based COVID-19 vaccines, inactivated vaccines may offer a potentially safer option for individuals with CAD.